2021
DOI: 10.1021/acs.energyfuels.0c03725
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Production of a Silicon Nanowire/Graphite Composites Anode via the CVD Method for High-Performance Lithium-Ion Batteries

Abstract: Aiming at preparing a cheap and high-performance anode material, a novel carbon-coated silicon nanowire on a surface of graphite microsphere composites was fabricated by employing a new silicon precursor via the chemical vapor deposition method. The chemical vapor deposition method could further reduce the cost and realize the large-scale preparation of silicon/graphite composites and simultaneously enhance the bonding strength between silicon and graphite. Due to the lower cost and lower requirement on equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Moreover, CVD technique has also been used to coat SiNPs and SiNWs with graphene to prepare Si-graphene composites for LIBs. [153,154] Zhang et al (in 2019) [153] used Si NPs diversely embedded in CVD-graphene film, which was fabricated into anodes for LIBs with high capacity. The reversible capacity of the anode was found to be reached 1115.2 mAh g −1 after six cycles.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CVD technique has also been used to coat SiNPs and SiNWs with graphene to prepare Si-graphene composites for LIBs. [153,154] Zhang et al (in 2019) [153] used Si NPs diversely embedded in CVD-graphene film, which was fabricated into anodes for LIBs with high capacity. The reversible capacity of the anode was found to be reached 1115.2 mAh g −1 after six cycles.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…However, it was observed that the anode lost the performance after six cycles due to its fragile structure. On the other hand, Liu et al (in 2021) [154] grew SiNWs on graphite microspheres and coated them with carbon using CVD technique to prepare carbon/SiNWs/graphite microspheres composite. The prepared composite exhibited excellent electrochemical performance.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…In the past several decades, the successful development and commercialization of electrochemical energy storage systems has promoted the revolution of portable electronic equipment and electric vehicles. Lithium-ion batteries (LIBs) have occupied the largest market of rechargeable batteries with their high energy density and good cycle stability. Nevertheless, the high cost, environmental pollution, and safety problems of LIBs have greatly hindered their further development. Therefore, clean, stable, and sustainable energy storage devices need to be developed . Aqueous zinc-ion batteries (AZIBs) have attracted much attention in the field of energy storage in recent years because of their advantages of high theoretical capacity, good safety, low cost, and water compatibility. …”
Section: Introductionmentioning
confidence: 99%
“…It has been widely studied in energy storage fields such as batteries and supercapacitors. 15,16 Ball milling, 17 chemical vapor deposition, 18,19 and electrostatic self-assembly 20,21 have been employed to allow for the effective bonding of graphene and Si, which brings great enhancement to the silicon-based anode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Graphene, a two-dimensional carbon-based material, has a large specific surface area, high mechanical strength, and excellent electrochemical properties. It has been widely studied in energy storage fields such as batteries and supercapacitors. , Ball milling, chemical vapor deposition, , and electrostatic self-assembly , have been employed to allow for the effective bonding of graphene and Si, which brings great enhancement to the silicon-based anode.…”
Section: Introductionmentioning
confidence: 99%